Ranashahi Prasasanik Karmachariko subidhama Biddyaman Asamanata ra Asantusti bare Prakash Parne Auta Sanad Sabal - Chalise, Pushparaj (Tribhuvan University Journal, 2011)
Available with fulltext. Key words: Rana System; Karmachari; Asamanata; Sanad sabal Tribhuvan University Journal Vol XXI, No. 2, 1998 Page: 155-161 Uploaded date: 29 April, 2011